Les formes de la guerre et la situation stratégique de l’Indien. Les armées des guerres de l’Indépendance dans les régions de la Plata au début du 19e siècle - Alejandro M. Rabinovich (Nuevo mundo - Mundos Nuevos, 2009)
After the 1810’s revolution and more so after the Central State’s collapse in 1820, the Río de la Plata’s society entered a long period of territorial fragmentation, revolutionary warfare and total militarization. This exploratory essay addresses the changes that occurred in Spanish-American’s military tactics, in order to better understand their impact upon the Indians’ strategic situation.